(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Diabetes mellitus is a group of metabolic disorders characterized by increased glucose levels over a prolonged period. The poly-herbal anti-diabetic tablet was formulated in the laboratory by using herbs of Enicostemma littorale (EL) (Gentianaceae), roots of Aconitum heterophyllum (AH) (Ranunculaceae), rhizomes of Picrorhiza kurroa (PK) (Scrophulariaceae), and fruits of Piper longum (PL) (Piperaceae). Furthermore, Laboratory formulation (LF) and Marketed formulations (MFs) were tested for Phytochemical screening and Qualitative chemical examination. From their result, isolation of active principles, Swertiamarin (EL-1) and Piperine (PN-1), was done and subjected to phytochemical examination by Modern analytical methods like TLC, UV, FTIR. Finally, the quantification and estimation of the afore-mentioned compounds were achieved by HPTLC. SSE of all the four formulations and the chemical tests proved alkaloids, flavonoids, carbohydrates, tannins, phenols and phytosterols. Comparing the data from the melting point, TLC, UV, and IR studies of EL-1 and PN-1 with standard Biomarkers, further calculation of both markers concentrations was done with the help of the calibration equation and the peak area derived from the chromatogram. Study outcomes signify that LF was more potent than MFs for anti-diabetic activity, signifying as a promising natural and safe remedy for the prevention of diabetic complications.